STRUCTURES IN THE NOVEL OF BIDADARI-BIDADARI SURGA BY KARYA TERE LIYE (Structuralism Analysis) - Nurul Azizah; Siti Gomo Attas; Herlina Herlina (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract This study aims to describe the character and characterization, plot, background, style of language, the point of view, theme and the mandate of Tere Liye's novel of Bidadari-Bidadari Surga. The method in this study is the content analysis of qualitative approach. Based on data analysis, the following results are summarized as follows: 1) The main character in Tere Liye's Novel of Bidadari-Bidadari Surga is Laisa, additional characters are Mamak, Babak, Dalimunte, Ikanuri, Wibisana, Yashinta. 2) The mixed flow, covering the situation Mother send Message to his children about the condition of the sickly Laisa, her mother sent to her children who message to he who received the first Message that Dalimunte, Ikanuri, Wibisana, and Yashintaberanjak adult, childhood continue to haunt them, climax that is Kak Laisa not yet married must pass by Dalimunte and his siblings. Dalimunte finally married after being forced by Kak Laisa. 3) The background consists of three sections, a backdrop of thirty-one backgrounds, a twenty-seven background setting, and a social setting that is a disgrace in the Lahambay Valley if an unmarried girl over the age of twenty. 4) The Language Style is the style of comparison, contradiction, and affirmation. 5) The third person's perspective